2015
DOI: 10.1515/abcsb-2015-0025
|View full text |Cite
|
Sign up to set email alerts
|

Morphological, Cytological and Embryological Characterization of F1 A. cepa × A. roylei Hybrids

Abstract: In the previous study we obtained a population of interspecific F1 A. cepa × A. roylei hybrids. In this study, in comparison to the parental species: A. cepa and A. roylei, the F1 hybrids were evaluated in terms of plant morphology, pollen viability, microsporogenesis and female gametophyte. Most of the morphological characters of the F1 hybrids were intermediate as compared to those of both parental accessions. In pollen mother cells (PMCs) of the F1 hybrids abnormalities were observed in meiosis as well as a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Therefore, with the aim of obtaining images of better quality, numerous clearing protocols that render plant tissues or organs translucent without disturbing their anatomy have been described, of which the use of methyl salicylate as a clearing agent is very common for studying ovules (e.g. [6, 7, 22, 52, 61]. The clearing technique is a quick and simple method frequently used in classical embryology to analyze ovule development, embryo sac formation, embryogenesis, and seed development [5, 6, 13, 16, 17].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, with the aim of obtaining images of better quality, numerous clearing protocols that render plant tissues or organs translucent without disturbing their anatomy have been described, of which the use of methyl salicylate as a clearing agent is very common for studying ovules (e.g. [6, 7, 22, 52, 61]. The clearing technique is a quick and simple method frequently used in classical embryology to analyze ovule development, embryo sac formation, embryogenesis, and seed development [5, 6, 13, 16, 17].…”
Section: Discussionmentioning
confidence: 99%
“…They display variations in traits such as disease resistance and tolerance to environmental stressors, traits that may be absent in cultivated varieties [ 3 ]. These traits can be incorporated into breeding programs to augment the adaptability and resilience of cultivated onions [ 45 , 46 , 47 ]. For instance, certain wild onion species such as A. asarense , A. roylei , A. galanthum , A. oschaninii , A. turkestanicum , A. pskemense , A. altaicum , A. farctum , A. praemixtum , A. rhabdotum , A. pskemense , and A. vavilovii demonstrate tolerance to harsh conditions such as drought, extreme temperatures, or poor soil [ 18 ].…”
Section: Onion Genetic Resourcesmentioning
confidence: 99%
“…All regenerants were subjected to molecular analysis to verify their hybrid status. en, F 1 hybrids were evaluated in terms of plant morphology, pollen viability, microsporogenesis, and female gametophyte development (Chuda et al, 2015;Kiełkowska, 2012;Kiełkowska & Adamus, 2010).…”
Section: Interspecific Crosses In Alliummentioning
confidence: 99%
“…Nuclear DNA analysis of the obtained progeny revealed that 98% of the regenerants were interspecific hybrids. Genomic in situ hybridization (GISH) revealed that hybrid plants possessed eight chromosomes identified as Allium cepa and eight chromosomes identified as Allium roylei (Chuda & Adamus, 2005, 2012Chuda et al, , 2015.…”
Section: Interspecific Crosses In Alliummentioning
confidence: 99%